English language skills development in a public institution. - Rodríguez Rodríguez, Ronaldo Ariel (2023)
The purpose of this case study is to investigate to determine the development of English language skills in public institutions in Ecuador. The factors to be analyzed come from the curriculum of the Ministerio de Educacion, which is designed to be implemented in public educational institutions, both for general basic education (5th to 7th) and General Unified High School (1st to 3rd). The development of English skills is fundamental for the acquisition of a second language, and it is also important that the level of English depends on the language skills that a person has, therefore it will also depend on the activities that are carried out in class. In public schools in Ecuador, planning is based on the prioritized curriculum imposed by the Ministry of Education in order to improve student learning, however both the teacher and the students play an important role in this learning process. During the present investigation, different points will be exposed, both positive and negative, to analyze the learning factors of the English language skills.